A Strategy for Coal Bed Methane and Coal Mine Methane Development and Utilization in China - Energy Sector Management Assistance Program (World Bank, Washington, DC, 2013)
China is short of clean energy, particularly conventional natural gas. The proven per capital natural gas reserve is only 1/12th of the world average. However, China has large coal bed methane (CBM) resources with development potential which can be recovered from surface boreholes independent of mining and in advance of mining, and also captured as a part of underground coal mining operations. However, in order to meet its targets, the government must improve the administrative framework for CBM resource management, introduce more effective CBM or coal mine methane (CMM) development incentives, raise the technical capacity of the mining sector, expand gas pipeline infrastructure and promote gas markets in coal mining areas. In order to significantly reduce methane emission from coal mines and better exploit the gas recoverable from coal seams, the government should introduce measures to: strengthen the CBM/CMM policy, legal and regulatory framework to improve resource management; improve CMM availability and quality so more can be utilized; enhance incentives to promote expansion of CBM/CMM exploitation and destruction of surplus drained CMM; and Promote development of regional development strategies to take advantage of specific local advantages.